THE EFFECTIVENESS OF ISLAMIC GUIDANCE AND COUSELING IN DEVELOPING STUDENT'S SELF-CONTROL (QUASI EXPERIMENT STUDY TOWARD THE STUDENTS GRADE VIII OF JUNIOR HIGH SCHOOL 9 CIMAHI) - Khatimah, Siti Ummi (2014)
The aim of this research is to know the effectiveness of the Islamic guidance and counseling in developing student's self-control in their study and interaction with friends at school. This research included the aspect of student's ability to manage the situation, that is about how to think and manage the situation when they are studying and interacting, the quality of student's motivation, patience and the student's abilityin accepting the consequences of their act or behaviour. The treatment which was conducted in this research is the islamic guidance and counseling with 'Targhib Wat Tarhib' technique and story telling technique. Islamic guidance and counseling is viewed as a guidance model which has the view about human being as a plenary creatures, the human beings who have a lot of virtues besides their weaknesses.The basic potential on human being is they have a natural character or 'fitrah'. It is the preference to correct themselves or the preference to have faith or 'Iman'. Islamic guidance and counseling is a comprehensive model because it all inclusive of human life. 'Targhib Wat Tarhib' technique and story telling technique, both techniques are originated from Al-qur'an and hadits. The result shows that there is a significant change on the students who are given the treatment compare with who are not. This shows that Islamic guidance and counseling is effective to use in developing student's self control and as one of models in counseling service in an Individual, Social, Study and career field. Furthermore, Besides mastering the techniques of Islamic guidance and counseling, the very important thing in conducting Islamic guidance and counseling is the personal characters of guidance and counseling teacher.